Conditional funding costs of inflation-indexed and conventional government bonds - Reschreiter, Andreas (Journal of Banking & Finance, 2004)
This paper employs the predictability of monthly excess returns of UK conventional and index-linked gilts to study the risk premiums of nominal and real bonds. The estimates of a single-latent-variable model suggest that indexed gilts of medium and long maturities require half the risk compensation of conventional gilts. The government can significantly reduce its long run borrowing costs through issuing inflation index-linked debt, however, the inflation indexation of bonds with maturities less than 3 years does not significantly reduce their risk compensation. Membership in the exchange rate mechanism did not significantly change the risk compensation of conventional and indexed gilts.